The Antibacterial Effect In Vitro of Honey Derived from Various Danish Flora - Reem Dina Matzen; Julie Zinck Leth-Espensen; Therese Jansson; Dennis Sandris Nielsen; Marianne N. Lund; Steen Matzen (Hindawi Limited, 2018)
The mechanism behind the biologic actions of honey as a wound remedy has been intensively studied; however, there is no published data regarding any antibacterial effect of honey derived from Danish flora. We surveyed 11 honeys of various Danish floral sources for their antibacterial activity and compared them to a culinary processed commercial honey (Jakobsens) and a raw and a medical grade Manuka (Leptospermum scoparium) honey using the agar-well diffusion method. We tested the effect on three gram-positive bacteria (two strains of Staphylococcus aureus and one strain of Staphylococcus epidermidis) and two gram-negative bacteria (Pseudomonas aeruginosa and Escherichia coli). All samples, except the commercial honey, exhibited antibacterial activity, and samples derived from Water Mint (Mentha aquatica), Organic 2 (mixed organic flora), and Linden (Tilia cordata) honey had consistent effects on all bacteria tested and showed greater effect than medical grade and raw Manuka (L. scoparium) honey. The content of methylglyoxal was low in the Danish honey (< 2 μg/mL) and significantly (p<0.05) higher in both the raw and the medical grade Manuka (L. scoparium) honey, where the concentrations were, respectively, 6.29 μg/mL and 54.33 μg/mL. The antibacterial effect of Danish honeys was mostly due to hydrogen peroxide. We conclude that honeys derived from Danish flora possess antibacterial effect, probably by a hurdle effect of viscosity, osmolality, acidity, bioactive peptides, and most importantly the content of hydrogen peroxide. These findings indicate that honeys of various Danish floral sources may have clinical potential, although further studies are necessary to elucidate this in order to determine whether the results of our in vitro experiments also apply to a clinical setting.